Energy infrastructure transitions with PV and EV combined systems using techno-economic analyses for decarbonization in cities. (1st August 2022) - Chang, Soowon; Cho, Junyoung; Heo, Jae; Kang, Junsuk; Kobashi, Takuro
Highlights: This study explores the decarbonization potential of rooftop PV combined with EVs. The system performance was evaluated using techno-economic analysis. The "PV + EV" system can reduce CO2 emissions and energy costs in Korean cities. The outcomes support prioritization among diverse building types in a city. The results guide technical and regulatory variables in the public and private sectors. Abstract: Rooftop photovoltaics (PV) and electric vehicles (EVs), and their combinations are highly effective technologies to decarbonize urban energy systems in a cost-effective way. However, it is not yet clear how these technologies can contribute to decarbonizing urban energy systems that are different in forms, building types, climate, culture, technical, and regulatory conditions. Therefore, we investigated the decarbonization potential of rooftop PV combined with EVs as batteries ("PV + EV") in five cases in Korea; four cities, and one province, from 2019 to 2030 using techno-economic analysis. We evaluated the energy, economic, and environmental performance of rooftop PV and EVs for the five built forms in Korea and different building types in Seoul. In addition, technical and regulatory variables (e.g., EV efficiency, feed-in-tariff, etc.) are optimized for multiple performances. The "PV + EV" system has been found to reduce CO2 emissions by up to 86% and energy costs by up to 51% within cities in Korea. In particular, residential buildings are found to have better performance in all aspects than those of other building types. This research provides governments and industries with urban decarbonization strategies and supports prioritization of the investment in suitable building types for the "PV + EV" system in a city.